Confined organometallic Au1Nx single-site as an efficient bifunctional oxygen electrocatalyst. (April 2018) - Liu, Lingyun; Su, Hui; Tang, Fumin; Zhao, Xu; Liu, Qinghua
Abstract: The development of organometallic complexes with abundant stable single-atom active sites is highly desirable for cost-effective and commercial electrocatalysis towards renewable energy conversion and storage. Here, we report an atomic-level design and construction of a new type of organometallic Au1 N x single-site confined on organic carbon-nitride support as a promising bifunctional electrocatalyst for efficient and durable oxygen reduction (ORR) and evolution reaction (OER) performance. The combination of atomic characterizations and theoretical calculations confirm that the atomically dispersed Au 1+ atoms are grafted onto carbon-nitride support by covalent Au–N bonds via an amine-induced-reduction strategy, forming atomic Au1 N x single-sites with potential oxygen-related catalytic activity. Hence, this developed Au1 N x single-site electrocatalyst could exhibit excellent electrocatalytic activity and durability with extraordinarily large mass activities of 9000 AgAu −1 for ORR at the half-wave potential 0.76 V, and of 1500 AgAu −1 for OER at overpotential 0.45 V, 20–26 times higher than those of benchmarking Pt/C and RuO2 electrocatalysts. Graphical abstract: We have designed a new type of atomic-level Au1 N x single-site confined on organic carbon-nitride as a promising bifunctional oxygen electrocatalyst. This developed atomic Au1 N x single-site electrocatalyst can achieve excellent electrocatalytic activity and durability with extraordinarily large mass activities of 9000 AgAu −1 for ORR at the half-wave potential 0.76 V and of 1500 AgAu −1 for OER at overpotential 0.45 V, 20–26 times those of benchmarking Pt/C and RuO2 electrocatalysts.fx1 Highlights: A new-type organometallic Au1 N x single-site is designed to realize highly efficient and durable bifunctional oxygen electrocatalytic performance. The atomic Au1 N x single-sites achieve extremely large mass activity of 9000 and 1500 A∙gAu −1 for oxygen reduction and evolution reaction, respectively, 20–26 times higher than those of benchmarking Pt/C and RuO2 electrocatalyst. A facile and ecofriendly "amine-induced reduction" strategy was developed to large-scale construct the atomically dispersed Au1 N x single sites. The combination of strong Au–N interaction and robust coupling effect between Au1 N x and carbon-nitride endows the atomic Au1 N x single-site with excellent redox catalytic activity and long-term durability for oxygen-involved catalysis.